The Overture to the Period of the Judges according to Josephus - Begg, C. (Liber Annuus, 2004)
Abstract Judg 1:1–2:5, with its alternative account of the events surrounding Israelʼs entry into the land, constitutes the overture to the Book of Judges. This study offers a detailed examination of Josephusʼ version of the biblical segment in his Ant. 5.120-135. The study focuses particularly on two overarching questions: which text-form(s) of Judg 1:1–2:5 did Josephus utilize? And what rewriting techniques has he applied to the biblical material in developing his own distinctive rendition of this?